Identifikasi Persepsi Wisatawan Terhadap Transportasi Wisata Saba Kota Cimahi (Sakoci) Di Kota Cimahi - Desy Oktaviani (Fakultas Ekonomi Universitas Garut, 2019)
Cimahi city tourism continues to experience rapid development, imahi city which has the nickname of the army city, trying to introduce Cimahi as a military triangle city to prospective tourists, with a unique way of launching tourist transportation in the form of buses called Sakoci, in march 2019 which aims which gives comfort, security and convenience to tourists when travelling in the city of Cimahi. Based on this, it is necessary to study the perception of tourism on lifeboat tourism transportation so that, it can be on target and beneficial, especially for the city of Cimahi tourism. The development of lifeboat tourism transportation is an effect and increased tourist demand is also a positive impact caused. Then it requires direction, especially regarding the needs and desires of tourists, thus it is deemed necessary to conduct research with the title identification of tourist perceptions of the transportation of the city of Cimahi Saba (lifeboat) in the city of Cimahi.This quantitative research was conducted in the city of Cimahi and aimed to identify tourists using lifeboats and reveal the perception characteristics and patterns of travel and tourist transportation. The researcher analyzes the data obtained by using the Importance Performance Analysis (IPA) method, this analysis method seeks to find which elements are considered important by tourists, so that suggestions and conclusions can be drawn for lifeboat transportation services. From this study produced an analysis of the type of tourist transport lifeboats received high attention from tourists. However, there are still many shortcomings that can reduce visitors on trips, uncertain visits, tours and frequency of tours as well as convenience of bus stop facilities, this needs specials attention to provide a good tourist experience and make tourists able to help to use lifeboats in the future.